2023
DOI: 10.1039/d3tb00568b
|View full text |Cite
|
Sign up to set email alerts
|

Diselenide-crosslinked nanogels laden with gold nanoparticles and methotrexate for immunomodulation-enhanced chemotherapy and computed tomography imaging of tumors

Abstract: It remains an extreme challenge to develop multifunctional drug delivery systems with tumor specificity and tumor microenvironment (TME) remodeling ability for improved chemotherapy against malignant tumors. Herein, we report the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It has been reported that both MTX and ROS are able to arrest the cell cycle. 40,41 To further explain the mechanism of cancer cell inhibition by LDH-MTX@CM M -Ce6 + US treatment, cell cycle changes in MCF-7 cells treated with different formulations were analyzed by flow cytometry (Fig. 3A and B).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that both MTX and ROS are able to arrest the cell cycle. 40,41 To further explain the mechanism of cancer cell inhibition by LDH-MTX@CM M -Ce6 + US treatment, cell cycle changes in MCF-7 cells treated with different formulations were analyzed by flow cytometry (Fig. 3A and B).…”
Section: Resultsmentioning
confidence: 99%
“…In a similar investigation, Jia et al designed diselenide-cross-linked poly ( N- vinylcaprolactum) nanogel co-loaded with gold NPs and methotrexate as a multifunctional nanoplatform for improved chemotherapy and computed tomography imaging tumors. The fabricated multifunctional material incorporated within the nanogel showed excellent colloidal stability under physiological conditions, while dissociating rapidly to release the incorporated gold NPs, and methotrexate effectively induces the apoptosis of cancer cells and prevents DNA replication, together contributing to the repolarization of macrophages from the protumor M2-like to antitumor M1-like phenotype in vitro ( Jia et al, 2023 ) . Therefore, the overall property of TA-SeNPs was retained in gel form and could be a potential candidate for topical biomedical applications.…”
Section: Resultsmentioning
confidence: 99%
“…The nanogel showed evident antitumour effects in a subcutaneous B16F10 tumour model through significantly disturbing DNA synthesis. 175 To further improve the therapeutic index of MTX, Wang and co-workers reported Fe-chelator histidine NPs, which could not only encapsulate MTX but also enhance the cytotoxicity of MTX by blocking the one-carbon metabolism (biosynthetic network) and de novo pyrimidine/purine synthesis (Fig. 10A).…”
Section: Metabolism-targeted Nanomedicine For Cancer Therapymentioning
confidence: 99%